ROTC Policy Regarding Homosexuals - Duemer, Lee S. (Education Policy Analysis Archives, 1997)
This is a policy analysis, in a historical context, of how Association of American University institutions responded to Reserve Officer Training Corps policy excluding homosexuals. The time period for this study is 1982 to 1992. Qualitative methods are used to analyze data and arrive at conclusions. Secondary data provide additional depth and background. This study reveals seven different positions institutions have taken in response to ROTC policy, these include: supporting ROTC policy, neutrality, collective action, barring military recruiters from campus, distancing the institution from ROTC, and changing the campus climate. This includes examples taken from AAU institutions and rationales behind making policy decisions.